Impact of COVID-19 on vegetable supply chain and food security: Empirical evidence from Bangladesh. - G M Monirul Alam; Most Nilufa Khatun (PLoS ONE, 2021)
In Bangladesh, the COVID-19 pandemic is likely to have substantial effects on the livelihood of people, but smallholder vegetables growers will be even more affected because of the perishability nature of the product. The first case of COVID-19 was confirmed in Bangladesh on 8th March, 2020 and consequently the country went into lockdown on 26 March, 2020. This study has made a survey of vegetables farmers through a mobile phone to understand the impact of COVID-19 on vegetables supply chain, gross margin and the future production plan of the growers. In Bangladesh, the lockdown has disrupted the food supply chain and increases the likelihood of food insecurity. Lockdown has impeded vegetable farmers' access to markets, thus limiting their productive and sales capacities. The price of yield has dropped by more than half resulting in huge loss for vegetable growers. The loss incurred by the farmers for producing Brinjal, Cucumber, Pointed gourd, Yardlong beans and Bottle gourd are BDT 4900, BDT 10900, BDT 57400, BDT 52500 and BDT 18500 per acre respectively as a result of COVID-19. The decreased income increases farmers' likelihood of vulnerability and food insecurity and poses a challenge to continued produce. 'Cash support' is more important than 'food support' in order to keep vegetable farmers in farming, to ensure a ready supply of necessary low-cost resources, and to help fight against the upcoming food shortage.